2D Layers of Group VA Semiconductors: Fundamental Properties and Potential Applications. Issue 1 (26th October 2022) - Batool, Saima; Idrees, Muhammad; Han, Su‐Ting; Zhou, Ye
Abstract: Members of the 2D group VA semiconductors (phosphorene, arsenene, antimonene, and bismuthine) present a new class of 2D materials, which are recently gaining a lot of research interest. These materials possess layered morphology, tunable direct bandgap, high charge carrier mobility, high stability, unique in‐plane anisotropy, and negative Poisson's ratio. They prepare the ground for novel and multifunctional applications in electronics, optoelectronics, and batteries. The most recent analytical and empirical developments in the fundamental characteristics, fabrication techniques, and potential implementation of 2D group VA materials in this review, along with presenting insights and concerns for the field's future are analyzed. Abstract : Members of the 2D group VA materials (phosphorene, arsenene, antimonene, and bismuthine) have presented their fascinating structures and intriguing electronic properties. The most recent analytical and empirical developments in the fundamental characteristics, fabrication techniques, and potential implementation of 2D group VA materials in this review, along with presenting insights and concerns for the field's future are analyzed.